Analisis Perilaku Konsumsi Siaran TV Digital di Kecamatan Pondok Tinggi Kota Sungai Penuh (representamen, 2023)
This research aims to assess the readiness of digital TV broadcast organizers in rural areas of Pondok Tinggi. The results are relevant for policymakers as a reference for digital broadcast regulations. Both government and private TV broadcasters can use these findings to transition from analog broadcasting. The method employed is a qualitative descriptive approach with a case study in Pondok Tinggi. Data was collected through interviews with residents of villages in Pondok Tinggi regarding content preferences, devices, and consumption factors. Data analysis involved 8 villages in the district. The research findings reveal that residents still prefer watching directly through digital TV rather than using gadgets, as it doesn't require expensive data and is considered free from fake news. Keywords: Behavior Analysis, Consumption Behavior, Digital TV Broadcasts